Acteurs et enjeux de la publicisation de la maladie d’Alzheimer - Mary Charoud (Communication)
Since the late 1990s the public construction of Alzheimer’s disease by the French daily press has become more political and fragmented. This article highlights these different views of the disease and their subsequent media coverage. A content analysis of French media publications between 1998 and 2008 reveals the dominant role of scientists and politicians in the portrayal of the disease while that of patients and their spokespersons is marginalized. Semi-structured interviews with journalists reveal the strategies involved in this public construction of the disease, as that of a social issue for the public at large.